VIRULENSI BERBAGAI ISOLAT JAMUR ENTOMOPATOGEN METARHIZIUM SPP. TERHADAP HAMA PENGGEREK BUAH KAKAO CONOPOMORPHA CRAMERELLA SNELL. (LEPIDOPTERA: GRACILLARIIDAE) - . Trizelia; . Nurbailis; Dina Ernawati (Universitas Lampung, 2013)
Virulence of various Metarhizium spp. (Deuteromycotina: Hyphomycetes) isolates on cocoa pod borrer pest, Conopomorpha cramerella Snell. (Lepidoptera: Gracillariidae). In Indonesia, Conopomorpha cramerella Snell. (Lepidoptera : Gracillariidae) is a serious pest of cocoa. Entomopathogens such as Metarhizium spp. (Deuteromycotina: Hyphomycetes) can be used to control this pest as an alternative to chemical insecticides. The purpose of this research was to study the virulence of isolates of Metarhizium spp. to pupae of C. cramerella. Nine isolates of Metarhizium spp each with 107 conidia/ml rate were used in the experiment. Pupal mortality was recorded daily. The results showed that isolate MetApCi from chili rhizosphere had the highest virulence causing 96.67% mortality of C. cramerella pupae and with an LT50 of 3.04 days.